Development of a facility for an advance competency in electrical engineering - Tuan Abdullah T.A.R.B.; Hamzah N.I.B. (2023)
This paper discussed the development of a facility for an advance competency in Electrical Engineering. The development was to fulfill the goal of the engineering education in an engineering college. The facility provided a facility to perform electrical network analysis, an industry size electrical network database and electronics communication devices. Firstly, this paper describes the methodology in formulating the advance competency and followed by a review on fundamental components of advance competency in electrical engineering including the network analysis, construction management and maintenance management. Subsequently, this paper presented a proposed method to assess the level of competency in engineering based on a supervised learning, where students worked to solve themes relevant to industrial problems. The problem is modeled by the test network in a database and electronic signals from the communication devices. Then the solution is formulated and tested based on the network analytical tools such as load flow, contingency, fault analysis, construction project maps and maintenance analysis. In conclusion, this paper discussed the competency gained by the students which include the evaluation of engineering design, assets maintenance, construction management and optimized decision in plant life management. The facility benefits the Electricity Supply Industry community and enriches the tertiary educational programs by exposing students to relevant competency towards global sustainability through efficient electrical network. 2009 IEEE.